Incentives for construction clients in Germany to choose concrete with recycled aggregates - Ellen Sterk (Philipps-University Marburg, School of Business and Economics, 2023)
Concrete with recycled aggregates ("R-concrete") offers a way to reduce the extraction of natural resources and to close material loops in line with political goals. However, market failures may hamper the efficient use of R-concrete in construction. Various policy instruments can be used in this situation to stimulate demand for R-concrete by construction clients and to correct market failures. This study aims to answer the question which instruments are potentially effective in this regard and how different client types differ in terms of their responsiveness to these instruments. The results show that all tested instruments have a positive effect in at least one of the client groups, but only financial incentives work over all groups. While information provision shows to have a positive effect on the likelihood to choose R-concrete (at least in some client groups), its effectiveness decreases with an increasing financial grant. Finally, client groups also differ in their general likelihood to choose R-concrete over conventional concrete. Conceiving of sustainability as an important criterion in construction projects increases this likelihood. This study offers a guideline for policy makers for the design of instruments in order to stimulate the use of recycled construction material.
Keywords: 330; Bauwirtschaft; Beton; Kreislaufwirtschaft; Deutschland